NECROTIZING ULCERATIVE GINGIVITIS AS A COMPLICATION OF FEBRILE NEUTROPENIA IN ACUTE MYELOID LEUKEMIA PATIENT - Desi Elvhira Rosa; Riani Setiadhi (FKG Unlam, 2023)
Background: Necrotizing ulcerative gingivitis (NUG) is a periodontal disease characterized by gingival pain, interdental gingival necrosis, and bleeding. NUG is closely related to immunosuppression, smoking, poor oral hygiene, malnutrition, and stress. Acute myeloid leukemia (AML) is a bone marrow malignant neoplasm. Chemotherapy as the treatment for AML often causes febrile neutropenia which results in immunosuppression conditions and is a risk factor for NUG. This case report aimed to discuss NUG as a complication of febrile neutropenia. Case: A 22-year-old woman was referred from hemato-oncology with acute myelomonocytic leukemia (AML-M4) and febrile neutropenia due to her oral complaints. She had undergone one cycle of chemotherapy and developed febrile neutropenia. Intra-oral showed ulcers covered with white-grayish plaques on the gingival region 35 to 45 and 15 to 25. There were white plaques that could be removed leaving an erythematous area on the dorsal tongue. Blood laboratory tests showed pancytopenia and severe neutropenia. The diagnoses were necrotizing ulcerative gingivitis and pseudomembranous candidiasis. Case management: Debridement using 1.5% hydrogen peroxide solution, rinsing with 0.2% chlorhexidine gluconate, as well as cleaning teeth and tongue 2 times daily. The internal medicine department gave meropenem. The lesions and gingiva were healed after three weeks of therapy. Conclusion: Febrile neutropenia due to chemotherapy reduces the body's ability to fight infection, oral homeostasis is disturbed therefore bacterial growth increases, neutrophils carry out phagocytosis forming reactive oxygen species which causing necrotic cells and then NUG occurred. Appropriate, adequate, and immediate therapy is needed to avoid further complications. Keywords: Acute myeloid leukemia, Febrile neutropenia, Necrotizing ulcerative gingivitis